Recombinant AgB8/1 ELISA test vs. commercially available IgG ELISA test in the diagnosis of cystic echinococcosis. (December 2013) - Tamarozzi, F.; Sako, Y.; Ito, A.; Piccoli, L.; Grisolìa, A.; Itoh, S.; Gatti, S.; Meroni, V.; Genco, F.; Brunetti, E.
Summary: The diagnosis and clinical management of cystic echinococcosis (CE) rely on imaging and serology, the latter still having a complementary role as its accuracy in assessing cyst viability is unsatisfactory. We used an experimental IgG ELISA test based on the recombinant antigen rEgAgB8/1 cloned from Echinococcus granulosus to differentiate active from inactive/cured CE infection, comparing its performance to that of a commercially available ELISA test used routinely in our hospital laboratory. Both tests were performed on sera from 88 patients with hepatic echinococcal cysts, grouped according to cyst stage based on ultrasonographical morphology, and on 17 patients surgically treated for echinococcosis and 18 patients with nonparasitic hepatic cysts included as controls. Tests' performances did not differ significantly, but the overall concordance between tests drastically dropped when groups were analysed separately. Further longitudinal studies should evaluate whether these discrepancies reflect the different ability of either test to predict the evolution of cysts over time. Although the recombinant‐AgB8/1‐based ELISA test seems to have no clinical advantage over the commercially available ELISA test in the assessment of hepatic CE cyst viability, the easiness of production and reproducibility of high‐quality recombinant antigens makes rEgAgB8/1 a valid candidate for use in CE ELISA diagnostic tests.